면역글로불린제제 국가출하승인을 위한 신규 B형간염표면항원항체가시험 유효성 확인 연구 - 성수경(Su Kyoung Seong); 김현정(Hyun Jeong Kim); 방윤수(Yun Su Bang); 손경희(Kyung Hee Sohn); 김영훈(Young Hoon Kim); 한기원(Kiwon Han); 최찬웅(Chan Woong Choi) (Yaghag-hoi-ji, 2024)
The quality control of plasma-derived medicinal products, including immunoglobulins, is a key element in the assurance of safety and efficacy of the final products. Among the test items, potency assay for anti-hepatitis B surface antigen has been conducted using various types of enzyme immunoassay systems. This study aimed to evaluate analytical method validation of enzyme-linked immunosorbent assay (ELISA) and electrochemiluminescence immunoassay (ECLIA) with auto-immunoassay analyzer. Two ELISA and one ECLIA kits, which were available domestically, were selected, and assays were validated using the national standard for human hepatitis B immunoglobulin. Specificity results showed a significant difference between matrix and 20 IU/L sample, indicating anti-hepatitis B surface antigen has no interference from matrix. For both intra-laboratory precision (day, analyst, and instrument) and inter-laboratory precision (reproducibility), the relative standard deviations (RSDs) were not more than 10% to the satisfaction of the three participating laboratories, although one ELISA kit showed higher RSD compared to other kits. Based on these results, both the ELISA and ECLIA can be applied for quality control tests performed by not only the manufacturer but also the national control laboratory as part of national lot release. It is expected that the current study will contribute to further strengthening the quality control capabilities for immunoglobulin products in Korea. KCI Citation Count: 0